Penegakan Hukum Bagi Pelaku Suap Menyuap Dengan Modus Transaksional Dalam Penerimaan Calon Kepala Desa - Kristin Doriana Simanjuntak; Amalia Syauket (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2024)
The criminal act of bribery corruption is committed due to transactions between the giver and recipient in exchange for money or as a kickback to speed up matters. Regarding law enforcement against perpetrators of corruption, bribery legally violates Article 12 letter a of Law No. 31 of 1999, amendment to UU No. 20 of 2001 concerning the Eradication of Corruption Crimes, the criminal penalties given are still too light, far from the expectations of justice for the community and do not optimize the effect. deterrent to perpetrators of bribery corruption in enforcing punishment. The purpose of this research is to find out bribery related to buying and selling positions which is a criminal act of corruption and to find out law enforcement against perpetrators of the criminal act of bribery related to buying and selling positions. This research uses normative juridical law which collects literature study data based on law by considering all relevant theories and rules related to bribery corruption with the types of primary, secondary and tertiary legal materials, concepts used by corruption, bribery and village head candidates. The results of the research concluded that buying and selling positions is a criminal act of corruption with transactions between the recipient and the giver using money as a means of transaction due to the lack of accountability and transparency in government and society. Therefore, in the future, the accountability system will be further cultivated by strengthening transparency in society so that criminal acts of corruption do not occur again.